Processing of the envelope glycoprotein gp160 in immunotoxin-resistant cell lines chronically infected with human immunodeficiency virus type 1. - Duensing, T D (1995)
We describe the isolation and characterization of variant cell lines which are chronically infected with the human immunodeficiency virus (HIV) and resistant to the action of immunotoxins directed against the HIV envelope protein. These variants all produce normal levels of HIV proteins, budding virions, and the envelope protein precursor gp160. Two of the variants, 10E and 11E, contain a mutation within the env gene which results in the production of a truncated precursor and altered processing and transport of the protein to the cell surface. Variants B9 and G4 are defective in gp160 cleavage and do not efficiently transport the envelope protein to the cell surface. There are no mutations in the expressed viruses of B9 and G4. These cell lines express higher levels of CD4 protein and mRNA than H9/NL4-3. Thus, 10E, 11E, B9, and G4 have escaped immunotoxin action by downmodulating the envelope protein from their cell surfaces. None of these variants produce infectious HIV. Two other immunotoxin-resistant variants, E9-3 and 41-17, produce normal levels of gp160, efficiently transport the cleaved and processed subunits to the cell surface, and secrete infectious HIV. These studies identify alterations in gp160 processing that underscore the importance of the relationship between HIV and the cell that it infects.